Indo-Nepal Trade: A Quantitative Analysis - Regmi, Udaya Raj (Administration and Management Review, 2009)
An attempt has been made to empirically analyze the Indo-Nepal trade position, using market share analysis, dependency ratio, trade intensity, complimentarity and country bias indices, degree of horizontal trade, comparative advantage, similarity index and intra-industry trade. India is loosing Nepal as the target market whereas Nepal has barely maintained its share in India. Owing to the existence of poor complementarity, Nepal's export composition could not match to that of import composition of India. Among the commodities that Nepal has comparative advantage, India has tended to remain the potential market only for a few commodities. Despite a shift in export composition, there is no possibility of horizontal trade between Nepal and India. The existing intra-industry trade linkages between these two countries are also very poor. In addition, the partial complementarity in export-import structures and the competitive export structure suggests that the prosperous expansion of trade between these countries can be achieved through vertical trade, harmonization of production structures, and change in trade and industrial policies. Administration And Management Review Vol 20, No.2 August 2008 Page:11-27